Tuberculosis ocular: un retrato portugués de este problema raro y desafiante - Kelly Lopes; Maria Inês Luz; Maria da Conceição Gomes (Sociedade Galega de Medicina Interna, 2023)
Abstract Objectives: Although threatening there is not enough awareness for ocular tuberculosis, hence we intend to study and characterize the ocular tuberculosis observed on a Portuguese specialized pulmonology diagnostic center. Materials and Methodologies: Retrospective study of individuals diagnosed with ocular tuberculosis and followed up from 1st January 2016 until 31th December 2018. Results: We studied 38 patients with presumed ocular tuberculosis, with mean age 53,3±15,7 years old, whose 55,3% where females. Seven patients had history of previous tuberculosis and only two patients reported a known risk contact. None had extraocular disease. All patients had at least one positive immunologic test, either tuberculin skin test (63,2%) or Interferon Gamma Release Assay test (86,8%). Most patients presented bilateral ocular tuberculosis (44,7%). The standard four-drug regime was the treatment of choice and corticosteroids were administered to 55,3% patient. The mean length of treatment was 8,6 months and among the patients who completed treatment, 72,4% presented clinical improvement or remission of the ocular manifestations. Conclusions: Ocular tuberculosis, despite a rare condition, carries a huge burden in health care centers. Delay in starting proper treatment can result in permanent blindness and impairment of life's quality. This condition is probably underdiagnosed and, to our knowledge, there is no recent studies characterizing the latest trend of ocular tuberculosis in Portugal. Resumen Objetivos: Aunque amenazante, no hay suficiente conciencia sobre la tuberculosis ocular, por lo que pretendemos estudiar y caracterizar los casos de tuberculosis ocular observados en un centro portugués de diagnóstico especializado en neumología. Materiales y Metodologías: Estudio retrospectivo de individuos con tuberculosis ocular seguidos desde 1 de enero de 2016 hasta 31 de diciembre de 2018. Resultados: Se estudiaron 38 pacientes, con una edad media de 53,3±15,7 años, de los cuales el 55,3% eran del sexo femenino. Siete pacientes tenían antecedentes de tuberculosis previa y dos pacientes reportaron un contacto de riesgo conocido. Ninguno tenía enfermedad extraocular. Todos los pacientes tenían al menos una prueba inmunológica positiva, ya sea prueba cutánea de tuberculina (63,2%) o prueba de interferón gamma (86,8%). La mayoría de los pacientes presentaron patología bilateral (44,7%). El régimen de cuatro fármacos fue el tratamiento de elección y se administraron corticoides al 55,3% de los pacientes. La duración del tratamiento fue de 8,6 meses y entre los que completaron tratamiento, 72,4% presentó mejoría clínica o remisión. Conclusión: La tuberculosis ocular, aunque una condición rara, sobrecarga los centros de salud. El retraso en el inicio del tratamiento puede provocar ceguera y deterioro de la calidad de vida. Esta condición probablemente está subdiagnosticada y, hasta donde sabemos, no hay estudios que caractericen su evolución en Portugal.